The citizen as a source of information: a case study on Jornal da Tarde, RTP - Mendes, Inês (2016)
Indispensable to news production, sources of information are complex and provide an interesting case review. Without them a journalist’s work would be next to impossible to perform since those sources are able to reinforce and give credibility to the news. In a time when the citizen’s participation in public service media is gaining more and more importance, this study aims to understand the kind of representation and prominence given to the citizen in the Portuguese television Public Service. In addition to understanding the presence of the citizen in Jornal da Tarde, RTP (Radio and Television of Portugal) the goal is to make a connection between the role of the Portuguese television Public Service and the need, or not, to call upon non-official voices to support the credibility and even the veracity of the topic in hand. In which topics the citizen’s voice is more present and which testimonials are more sought after by RTP are some of the topics under discussion. In order to do that – identify the news in which the citizen’s voice was used and to find answers to the given question – a content analysis of 21 broadcasts of Jornal da Tarde was performed.